Pengolahan Citra Digital EKG Rumah Sakit Tk.IV Samarinda - Setyowati, Anggriya Feby; Wardani, Pratiwi Sri; Putri, Erlinda Ratnasari; Putri, Devina Rayzy Perwitasari Sutaji (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2024)
In the hospital itself, especially in the MCU Poly Radiology Installation, it is a unit that performs services such as Medical Check Up, making health certificates, and carrying out routine checks at an institution. ECG examination is one of the services most frequently performed routinely by patients. Examinations carried out include medical check-ups, monitoring of long-term therapy, patient to assessment before surgery, individual screening for high-risk jobs, examinations before participating in sporting events, and overall examinations as a condition of employment. This study carried out the process of withdrawing information or object descriptions or identifying objects contained in images by compressing or reducing image data. By using EKG data from TK.IV Samarinda Hospital by carrying out processing stages such as converting analog data to digital, cropping, and applying filters to EKG images. After the filter is applied to the image, it is found that after 5 types of image processing (RGB Image, Grayscale Image, Binary Image, Thresholding Image, and Edge Detection Image) on the results of the ECG signal it can be concluded that the processed signal retains the features of the existing signal and information. . Of the five types of processing methods, the clearest result is conversion to Edge Detection imagery.